A Analisis Faktor Yang Mempengaruhi Pertumbuhan Ekonomi Indonesia Tahun 1991-2020 - muna, ibnu choiru (LPPM Universitas Muhammadiyah Mamuju, 2023)
Economic growth is one of the indicators in the success of development in a region. Indonesia's economic growth during the period from 1991 to 2020 was volatile but had a stable tendency. The purpose of this study is to analyze what factors affect economic growth in Indonesia and find out the relationship between the variables that affect it. This test was carried out using an analytical descriptive method with a quantitative approach and using secondary data published by the World Bank Data from 1991 to 2020. The time series data in this test was processed using eviews software with the ECM (Error Correction Model) method using the ARDL (Autoregressive Distributed Lag) model. From the result of simoultanous test, all the variables that contain of labour participation rate, consumtion, and unemployment as independent variable have a long term influence on economic growth as dependent variable on Indonesia's economic growth in 1991-2020